Mandatory Custody Mediation in San Diego, California, 1996 - Saccuzzo, Dennis P. ([Verlag nicht ermittelbar], 2010)
The purpose of the study was to provide empirical data to inform the debate and lead to meaningful answers to questions in custody mediation and domestic violence including equity of outcomes for families with partner violence versus those without any evidence of violence, and the issue of health and safety outcomes for the children. Researchers examined every seventh action filed in the Family Court in San Diego during the calendar year 1996. Each of the 512 nonagreement mediation reports and its associated Court Screening Form were scanned in its entirety and subsequently printed. Each report also contained an appended page, containing a detailed parenting plan in which the mediator summarized the percentage of physical custody recommended for each parent. Each report was studied and content analyzed by three trained raters who had no access to the Court Screening Form and so were blind to any a prior domestic violence allegations. The majority of coding items called for yes/no responses. Other coding items allowed the raters to choose from among more than two options. A variable was coded in a particular direction if all three raters agreed or if two of the three raters agreed. The domestic violence sample (n = 200) included all of the selected cases with domestic violence indicators on the current screening form, prior allegation of domestic violence on a court screening form and/or a permanent domestic violence restraining order in the case file that was available to the mediator, and clear cases of domestic violence as documented by the mediator in which there was absolutely no indication of domestic violence on any screening form or in the case file. The nondomestic violence sample (n = 200) included 200 of the remaining 312 cases that had no indicators of domestic violence in the file and no mention of domestic violence in the mediation report. The data includes five categories of variables: general case information, parental factors, child factors, family interaction factors, and current parental relationship.